Brain mapping of deception and truth telling about an ecologically valid situation: functional MR imaging and polygraph investigation--initial experience - Mohamed, Feroze B; Faro, Scott H; Gordon, Nathan J; Platek, Steven M; Ahmad, Harris; Williams, J Michael (Radiology, 2006)
To examine the neural correlates during deception and truth telling by using a functional magnetic resonance (MR) imaging technique and an ecologically valid task and to compare the results with those of a standard polygraph examination. All subjects gave written informed consent for this HIPAA-approved study, which was approved by the institutional review board of Drexel University. Eleven healthy subjects (five female and six male subjects; mean age, 28.9 years) were randomly assigned to the group of guilty subjects or the group of nonguilty subjects. Each group consisted of two separate functional MR imaging conditions: "lie-only condition" and "truth-only condition." The lie-only condition was used to compare brain activity during a known lie to control questions and a subjective lie to relevant questions. The truth-only condition was used to compare brain activity during a known truthful response to control questions and a subjective truthful response to relevant questions. Functional MR images were acquired with an echo-planar sequence, and statistical analysis was performed. Physiologic responses were measured with a standard four-channel polygraph instrument. During the deception process, specific areas of the frontal lobe (left medial and left inferior frontal lobes), temporal lobe (right hippocampus and right middle temporal gyrus), occipital lobe (left lingual gyrus), anterior cingulate, right fusiform gyrus, and right sublobar insula were significantly active. During the truth telling process, specific areas of the frontal (left subcallosal gyrus or lentiform nucleus) and temporal (left inferior temporal gyrus) lobes were significantly active. The polygraph examination revealed 92% accuracy in deceptive subjects and 70% accuracy in truthful subjects. Specific areas of the brain involved in deception or truth telling can be depicted with functional MR imaging.